Clay tokens - accounting before writing in Eurasia - Budja, Mihael (Documenta Praehistorica, 1998)
A number of small ceramic and stone objects of rather uniform shape, which have been interpreted in Near and Middle Eastern archaeological contexsts as counters used for calculating quantities of goods in systems of exchange are discussed in European interpretative contexts of the transition to farming and the secondary product scenario.
Keywords: archaeology; arheologija; arheološke najdbe; Europe; Evropa; neolitik